EKSISTENSI PENGHUBUNG KOMISI YUDISIAL NUSA TENGGARA BARAT DALAM MELAKUKAN PENGAWASAN KODE ETIK HAKIM - Habibi, Habibi (Jurnal Muhakkamah, 2020)
This study intends to find out the existence of the West Nusa Tenggara judicial commission (PKY) liaison in maintaining and overseeing the behavior of judges. The method used by the writer is juridical-normative. The results of this study can be concluded that in general PKY is a supporting institution under the Judicial Commission (KY). PKY is included in an additional supporting institution. This is based on Article 24B of the 1945 Constitution which gives authority to KY to form a supporting institution. The liaison officer of the West Nusa Tenggara Judicial Commission has the duty to receive public reports, conduct court monitoring, judge advocacy and other tasks given by the RI Judicial Commission. Factors influencing the liaison of the West Nusa Tenggara Judicial Commission to carry out their duties and functions in realizing Clean Judiciary, there are inhibiting and supporting factors, inhibiting factors include insufficient human resources and lacking liaison budgets, while inhibiting factors include Human Resources, Collaboration and Professionalism , and the Judicial Commission Network, a small area and court.